Curative effects of RF combined with DSA-guided ethanol sclerotherapy in venous malformations - Wang, Xing (Exp Ther Med, 2016)
The aim of the study was to investigate the clinical effect of radiofrequency (RF) ablation combined with digital subtraction angiography (DSA)-guided anhydrous ethanol injection sclerotherapy in the treatment of high-return flow venous malformation (VM). Forty-one patients who were diagnosed as high-return flow VM with clinical and radiographic evidence were divided into the observation group (n=19) and control group (n=22) by random number table. All the patients received DSA-guided anhydrous ethanol injection sclerotherapy while the patients in the observation group were given RF ablation in addition. The clinical effect, treatment times and adverse effects of the two groups were analyzed. The effectiveness of the observation group was significantly higher than that of the control group (94.7 vs. 81.8%). Facial paralysis occurred in three patients (13.6%) after ethanol injection in the control group, while the observation group had no facial nerve injury after treatment. The patients in the observation group had significantly fewer number of ethanol injections. RF can improve the efficacy of high-return flow VM and reduce the number of ethanol injections. The scheme is safe and effective, which is worth expanding in clinical practice.